Reimaging Primary Health Care Workforce in Rural and Underserved Settings - Strasser, Roger; Strasser, Sarah (World Bank, Washington, DC, 2020)
This Discussion Paper starts at the local level and reimagines primary health care (PHC) and the PHC workforce from the perspective of people living in rural and underserved urban areas of low- and middle-income countries (LMICs). Drawing on research evidence and successful examples, it presents a “start local” health service delivery model, health system design framework, and financing models intended to ensure high-quality local comprehensive PHC is available and accessible to all. Core PHC team members (community health workers, registered nurses, specialist family physicians, and administrators) and other health practitioners are generalists in their disciplines, working together in collaborative practice as the frontline providers of care that responds to the health needs of the population they serve. The most successful model of education and training for local comprehensive PHC is socially accountable, immersive community-engaged education woven into a facilitated education and training pathway starting with recruiting local students from rural and underserved communities. Successful attraction, recruitment, and retention of PHC team members results from the systematic approach of the Workforce Stability Framework with the three main tasks of plan, recruit, and retain supported by a long-term strategy and five conditions for success. High-quality local comprehensive PHC is successful in improving local population health when it is part of an integrated health system that connects clusters of autonomous local health service delivery organizations through partnerships with regional referral centers and other specialist service organizations that value the expertise of local PHC providers. All levels of the health system (local, regional, and national) are enhanced by intersectoral collaboration with active participation of all Partnership Pentagram members (policy makers, health administrators, health professionals, academics, and communities), underpinned by a local health needs, focused national health strategy, up-front local investments in PHC infrastructure and personnel, and funding models that reward achieving health outcomes.